A computerized image database for freshwater algae recorded in Turkey - Sen, Bulent; Sonmez, Feray; Cetin, Ahmet Kadri; Alp, Mehmet Tahir; Ozer, Tulay Baykal; Yildiz, Kazim; Cevik, Fatma (Tubitak Scientific & Technological Research Council Turkey, 2015)
A computer-based image database for freshwater algae recorded in Turkey has been established. A separate page was prepared for each algal taxon and each page includes images and taxonomic and ecological information related to the taxon. Algal images were obtained mainly from authors of algal studies previously carried out in various freshwater bodies in Turkey. Data were then standardized in accordance with that of the central database of Turkish herbaria and a database for Turkish freshwater algae, which were previously established through TUBITAK projects. The database program Access was used to enter data, as this program recognizes Turkish characters. A total of 627 data with images were installed in the database. These belonged to Bacillariophyta (202 data), Chlorophyta (255 data), Chrysophyta (3 data), Cryptophyta (2 data), Cyanophyta (87 data), Dinophyta, (12 data), Euglenophyta (61 data), Prasinophyta (1 datum), Rhodophyta (1 datum), and Xanthophyta (3 data).
Keywords: Image database; freshwater algae; Turkey